Energy - Challoner, Jack. (New York : Dorling Kindersley, 1993)
Text accompanied by photographic illustrations survey various sources of energy and the ways in which they have been harnessed.
Muscle energy -- Potential energy -- Electromagnetism -- Thermodynamics -- Measuring energy -- Energy from food -- Alternative energy.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
8.9
4-6
Keywords: Power resources -- Juvenile literature; Force and energy; Power resources; Energy resources; Force and energy